Irish America - Byron, Reginald (Oxford studies in social and cultural anthropology., 1999)
"This study, based on interviews with 500 people of Irish ancestry in Albany, New York, aims to discover in what senses and in what degrees the present-day descendants of nineteenth-century Irish immigrants possess distinctive social practices and ways of seeing the world, and raises questions about the social conditions in which ideas of Irishness have been created and recreated."--Jacket